British Gynaecological Cancer Society Recommendations for Women With Gynecological Cancer Who Received Non-standard Care During the COVID-19 Pandemic. Issue 3 (March 2022) - Taylor, Alexandra; Sundar, Sudha S.; Bowen, Rebecca; Clayton, Rick; Coleridge, Sarah; Fotopoulou, Christina; Ghaem-Maghami, Sadaf; Ledermann, Jonathan; Manchanda, Ranjit; Maxwell, Hilary; Michael, Agnieszka; Miles, Tracie; et al.
Abstract : (Abstracted from Int J Gynecol Cancer 2022;32:9–14) Because of the overwhelming pressure placed on the health care system during the COVID-19 pandemic, resource prioritization and infection risk led to deviation from standard of care treatment for women with gynecologic cancer. The loss of intensive care availability, surgical capacity, as well as radio- and systemic therapy availability particularly impacted this vulnerable population.